Synthesis of Si02 nanopowder from rice husk ash - Ruksudjarit A. (2014)
In the present work, we demonstrate a method to synthesis SiO2 nanopowder from rice husk ash by using a vibro-milling followed by a heat treatment technique. Rice husk ash was milled by vibro-milling for 4 h to obtain nanopowder. In order to eliminate carbonaceous material, the nanopowder was heat at lOOO°C for 3 h. Characteristic of the powder was then investigated by XRF, XRD, and SEM techniques. The silica nanopowder with 95% purity was obtained after the heat-treatment. The result indicated that the present method is a beneficial process to produce the silica nanopowders of low cost and high mass productivity. © 2008 Trans Tech Publications, Switzerland.